Health, Science, and Place : A New Model - Blatt, Amy J. (Geotechnologies and the Environment ;, 2015)
The main focus of this monograph is synthesizing the importance of geographic approaches to public health and patient care.  The chapters are organized into four themed sections:  the role of geography in health care reform; the geographies of human health; geospatial data and technologies; and geography in medicine.  It is a highly informative book, providing scientific insight for geographers with an interest in advanced geospatial applications and health research.  The author is an international expert in geography, GIS, and public health, who recently co-edited a special issue on "Geospatial Applications in Disease Surveillance," published in the International Journal of Applied Geospatial Research.